SAFEGUARDING URBAN COMMUNITIES FROM THE PHYSICAL AND PUBLIC HEALTH IMPACTS OF UNREGULATED RESIDENTIAL MANHOLE CONSTRUCTION ALONG ACCESS ROADS - MUSTAPHA MUHAMMAD (Journal of Human, Social and Political Science Research, 2026)
Rapid urban expansion in developing countries has intensified the construction of individual residential sanitation infrastructure, particularly manhole pits, along access roads. While these facilities are essential for household wastewater management, their unregulated construction often creates significant physical hazards, environmental degradation, and public health risks that undermine sustainable urban development. This study assessed the physical and public health impacts of rapid residential manhole construction along access roads in Kwado Settlement, Katsina State, Nigeria. A mixed-method cross-sectional research design was adopted, integrating household surveys, field observations, and stakeholder interviews. Primary data were collected from 300 households selected across ten neighborhoods within the settlement using structured questionnaires and observation checklists. The collected data were analyzed using descriptive statistics, Relative Importance Index (RII), reliability analysis (Cronbach's alpha), chi-square test of association, and multiple regression analysis to evaluate the relationships between construction practices and community health outcomes. The findings revealed that road obstruction (RII = 0.91), stagnant water accumulation (RII = 0.88), construction waste deposition (RII = 0.86), dust generation (RII = 0.84), and unprotected manhole excavations (RII = 0.82) were the most critical physical hazards affecting residents. Health-related impacts included mosquito-borne diseases (61%), accidental injuries (54%), respiratory discomfort (47%), eye irritation (45%), and psychological stress associated with unsafe neighborhood conditions (43%). Inferential analysis demonstrated a statistically significant relationship between unsafe residential manhole construction practices and adverse community health outcomes (χ² = 36.42, p < 0.001), while the regression model indicated that road obstruction, stagnant water, and uncovered excavations were significant predictors of perceived health and safety risks. The study concludes that although household manhole construction contributes to improved sanitation, inadequate planning, weak regulatory oversight, and poor compliance with construction safety practices collectively generate substantial risks to urban infrastructure, environmental quality, and community well-being. The study proposes a community-based residential construction safety framework that integrates planning approval, engineering standards, environmental monitoring, and community participation to enhance urban resilience. These findings contribute to the growing body of knowledge on sustainable urban infrastructure management and provide evidence-based recommendations for policymakers, urban planners, environmental regulators, and local governments seeking to improve residential construction governance in rapidly urbanizing communities.